Sustained Improvement in Inflammatory Bowel Disease Quality Measures Using an Electronic Health Record Intervention - Bensinger, Andrew; Wilson, Farra; Green, Patrick; Bloomfeld, Richard; Dharod, Ajay (Applied clinical informatics, 2019)
Abstract Background Inflammatory bowel disease (IBD) is a chronic condition with wide variation in treatment and resource utilization because of many different disease presentations and treatment options. In an effort to standardize care and improve health outcomes, several organizations have created performance measures to monitor various aspects of IBD care. Objectives We aimed to assess longitudinal documentation adherence with physician quality reporting system's (PQRS) IBD performance measures before, immediately after, and 1 year following the implementation of a comprehensive electronic health record (EHR) IBD clinical documentation support tool intervention. Methods We reviewed 50 patient charts that were randomly selected from consecutive outpatient IBD visits at our tertiary care center from September 1, 2015 to June 30, 2016, prior to implementation of an IBD-specific note template, order set, and patient education handout on September 1, 2016. Two additional cohorts of 50 patient charts were randomly selected from September 1, 2016 to June 30, 2017 and September 1, 2017 to June 30, 2018. These charts were reviewed to assess adherence of pertinent PQRS performance measures for outpatient IBD care. The project was deemed not human subjects research and received exempt approval by the Institutional Review Board (IRB#: IRB00040399). Results The cohort immediately after the intervention showed significant increases in documentation rates of influenza immunization (19–59%, p < 0.001), pneumococcal immunizations (2–38%, p < 0.001), tobacco cessation (28.6–77.8%, p = 0.049), and proportion of all eligible measures (40.6–62.2%, p < 0.001) when compared with the preintervention group. Moreover, documentation rates were sustained in the 1-year follow-up group when compared with the postintervention group. Conclusion A multifaceted, EHR focused approach can significantly and sustainably improve documentation of outpatient IBD quality measures.